2007
DOI: 10.1007/s11434-007-0503-7
|View full text |Cite
|
Sign up to set email alerts
|

Studies on treatment of chlorophenol-containing wastewater by microbial fuel cell

Abstract: A microbial fuel cell with 4-CP as oxidant was established to investigate the feasibility of 4-CP dechlorination in the cathodic chamber of MFC. It demonstrated good performance on electricity generation with P max 12.4 mW/m 2 and CE 22.7%. Besides, 60 mg/L 4-CP could be completely dechlorinated in 45 h in the MFC, and 4-CP dechlorination process and electricity generation process had obvious synergistic effect. microbial fuel cell, chlorophenol, oxidant, dechlorination Microbial fuel cell (MFC) is a device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…41,42 Nitrobenzene, azo dye of Acid Orange 7 and chlorinated organic of 4-chlorophenol can be reduced in an abiotic cathode, with concomitant energy recovery. 24,25,43,44 pH at the cathode was proved to strongly affect power production and removal of these recalcitrant wastes. 24,25 Additionally, the reductant usage ratio defined as the ratio of electrons available at the anode and consumed at the cathode was 3-6 times as high as the theoretical values, indicating the inefficiency of anodic electrons.…”
Section: Recalcitrant Wastes Treated In Bess Abiotically Cathodic Mfcsmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 Nitrobenzene, azo dye of Acid Orange 7 and chlorinated organic of 4-chlorophenol can be reduced in an abiotic cathode, with concomitant energy recovery. 24,25,43,44 pH at the cathode was proved to strongly affect power production and removal of these recalcitrant wastes. 24,25 Additionally, the reductant usage ratio defined as the ratio of electrons available at the anode and consumed at the cathode was 3-6 times as high as the theoretical values, indicating the inefficiency of anodic electrons.…”
Section: Recalcitrant Wastes Treated In Bess Abiotically Cathodic Mfcsmentioning
confidence: 99%
“…24,25 Additionally, the reductant usage ratio defined as the ratio of electrons available at the anode and consumed at the cathode was 3-6 times as high as the theoretical values, indicating the inefficiency of anodic electrons. 43 Fine-tuning of the anodic potential and loading will allow minimization of the electron losses and thus improve the performance of BESs for recalcitrant wastes treatment. 24,25,37 Besides the recalcitrant organics, some recalcitrant heavy metals with high redox potentials such as Cr(VI), V(V), Cu(II), U(VI) and Se(VI) can also be successfully used as electron acceptors in abiotically cathodic MFCs.…”
Section: Recalcitrant Wastes Treated In Bess Abiotically Cathodic Mfcsmentioning
confidence: 99%
“…And a maximum power density of 115.6 mW/m 2 was generated [27]. Gu et al revealed that a maximum power density of 12.4 mW/m 2 was generated using 50 ppm chlorophenol as the electron acceptor [28]. In contrast to potassium permanganate and chlorophenol, potassium dichromate was a more favorable electron acceptor, showing a higher power density of MFC.…”
Section: Effects Of Initial Cr 6+ Concentration On Output Power Densimentioning
confidence: 99%
“…Therefore, if using certain pollutant with the ability of accepting electrons and protons as oxidant, the cathode chamber of MFCs, as well as the anode chamber could harvest considerable energy from pollutants. This would greatly enhance the environmental benefit of MFCs [28]. Based on this hypothesis, electroplating wastewater containing Cr 6+ was chosen as the cathodic electron acceptor in this study.…”
Section: Introductionmentioning
confidence: 99%
“…They have been considered as priority water pollutants by the United States Environmental Protection Agency (EPA) and Environmental Monitoring of China, because of their high toxicity to organisms at low concentrations [3,4]. Since most of the dyes are biologically non-degradable, it is difficult to remove them from wastewater.…”
Section: Introductionmentioning
confidence: 99%